ANALISIS EKUITAS MEREK KOMUNIKASI PEMASARAN TERPADU PADA MODA OJEK ONLINE ‘’GRAB’’ - DWI MUHAMMAD TAQWA; HARDYANSYAH (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The purpose of this research are to: 1. To study and analyze the Brand Equity of Grab online ojek equity in Palembang, 2. To study and analyze the Integrated Marketing Communication of IMC Ojek Grab Online in Palembang.